Keep Spirit, Even Though Covid-19 is in Your Life (Phenomenological Study on Covid-19 Survivors in Malang City) - Indira Ravly Rezaputra; Romie Mukti Qadafi; Latipun Latipun (PT Publikasiku Academic Solution, 2023)
Covid-19 is a disease that attacks the human respiratory system. The condition is caused by a virus called SARS-CoV-2, which is characterized by cough, fever, fatigue, and loss of smell. This study aims to understand the life journey of COVID-19 survivors, how they can survive in difficult times and what are the underlying things using a phenomenological approach. In conducting qualitative phenomenological research, four processes are passed: phone, phenomenological reduction, imaginative variation, and synthesis of meaning. In analyzing and interpreting the data by bracketing, horizontal exploring, meaning unit to get a structural description, innovative take to get a structural elucidation, and combining it to make a universal meaning and represent the respondent's experience. The selection of respondents using purposive sampling with the number of subjects three new students. The data collection instrument used a tape recorder with in-depth interview data collection techniques. The results of this study state that there are various ways that respondents have done in dealing with the covid-19 pandemic for themselves and their families, there is motivation as encouragement in themselves to be able to recover from the coronavirus, the role of the family as an emotional boost for respondents to achieve recovery, and still the lack of knowledge possessed by the community related to the transmission of the coronavirus and health protocols which resulted in a miss perception of covid survivors